(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Today, precious stones and jewellery is a global industry, with gold, diamonds, platinum mining operations in Africa, Russia, Canada and Australia, Poland and the jewellery industry in the United States, Israel, China, India and Turkey, as well as retail sales around the world. Customer Relationship Management (CRM) is a combination of policies, processes, and strategies implemented by an organization to unify its customer interactions and provide a means to track customer information. Customer Relationship Management (CRM) is an emerging tool that enables marketers to maintain their presence in the dynamic marketing environment. The goal of Customer Relationship Management (CRM) is to ensure customer satisfaction & delight at every level of interface with the company/shop. Customer Relationship Management (CRM) is high on the corporate agenda. This research is descriptive in nature. A study on customer satisfaction towards supply chain management practices in jewellery sector. The present study focuses on customer satisfaction towards supply chain management practices in jewellery sector. The Primary data and secondary data were used for the study. Primary data was collected using a structured questionnaire and the secondary data from journals, websites and newspapers. The data was collected from 80 respondents belongs to the selected area of Kanyakumari District. The collected data were analyzed using percentage analysis and Garret ranking in order to draw the inference of the study.